Five new species, one new genus, two synonymies, and new distributional records in Cerambycidae (Coleoptera) - Martins, Ubirajara R.; Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2016)
Five new species, and one new genus of Cerambycidae are described: Drycothaea vulcanica sp. nov. (Calliini), from Ecuador (Holotype male deposited in AMNH: Napo, 29.X.1988, J.S. Miller leg.); Perissomerus machadoi sp. nov. (Neoibidionini), from Paraguay (Holotype male deposited in MZSP: Alto Paraguay, 30.XI.2002, Di Iorio leg.); Cacostola carinata sp. nov. (Onciderini), from Brazil (Holotype female deposited in MZSP: Rio Grande do Norte, IX.2008, D.R.R. Fernandes et al. leg.); Ypomacena gen. nov. (Apomecynini) from Brazil to include Y. monnei sp. nov. (Holotype male deposited in MNRJ: Bahia, XI.1970, Roppa leg.), and Y. gibbosa sp. nov. (Holotype female deposited in MNRJ: Rio de Janeiro, 31.X.1969, Alvarenga & Seabra leg.). Dorcasta prolongata Fisher, 1947 is proposed as a new synonym of Bebelis lignea (Bates, 1866). Bisaltes (Bisaltes) fuchsi Breuning, 1971 is proposed as a new synonym of Bisaltes (Bisaltes) buquetii Thomson, 1868. Additionally, sixteen new states records for Brazil, and three country records for Bolivia are provided.